MIND Diet Impact on Multiple Sclerosis Patients: Biochemical Changes after Nutritional Intervention - Navarrete-Pérez, Ainoa; Gómez-Melero, Sara; Escribano, Begoña Mª; Galvao-Carmona, Alejandro; Conde-Gavilán, Cristina; Peña-Toledo, Mª Ángeles; Villarrubia, Noelia; Villar, Luisa Mª; Túnez, Isaac; Agüera-Morales, Eduardo; Caballero-Villarraso, Javier (International journal of molecular sciences, 2024)
There is substantial evidence supporting the neuroprotective effects of the MIND diet in neurodegenerative diseases like Parkinson’s and Alzheimer’s. Our aim was to evaluate the impact of a nutritional intervention (NI) with this diet on multiple sclerosis (MS) patients. The study was conducted in two stages. In the first stage, two groups were included: MS patients before the NI (group A) and healthy control subjects (group B). In this stage, groups (A) and (B) were compared (case–control study). In the second stage, group (A) was assessed after the NI, with comparisons made between baseline and final measurements (before-and-after study). In the case–control stage (baseline evaluation), we found significant differences in fatigue scores (p < 0.001), adherence to the MIND diet (p < 0.001), the serum levels of brain-derived neurotrophic factor (BDNF) (p < 0.001), and higher oxidative status in the MS group, with lower levels of reduced glutathione (p < 0.001), reduced/oxidised glutathione ratio (p < 0.001), and elevated levels of lipoperoxidation (p < 0.002) and 8-hydroxy-2′-deoxyguanosine (p < 0.025). The before-and-after intervention stage showed improvements in fatigue scores (p < 0.001) and physical quality-of-life scores (MSQOL-54) (p < 0.022), along with decreases in the serum levels of glial-derived neurotrophic factor (GDNF) (p < 0.041), lipoperoxidation (p < 0.046), and 8-hydroxy-2′-deoxyguanosine (p < 0.05). Consumption of the MIND diet is linked to clinical and biochemical improvement in MS patients.